Educazione e mondo del lavoro. Figure di accompagnamento e potenzialità delle nuove tecnologie nei servizi di bilancio delle competenze e nell'orientamento professionale - Limone, Pierpaolo; Pace, Rosaria; Rita Mangione, Giuseppina (Media e tecnologie per la didattica - Open Access, 2016)
The second volume of a double editorial project: while the first is dedicated to the relationship between the methodological-didactic, technological and organizational dimensions in the process of school innovation, the latter is dedicated to the inclusive education teachers and the role of technology in the services of skills assessment and career guidance. Its aim is to interpret and support the relationship between school and work.